Assessing Passenger Electric Vehicle Growth Strategies and Their Impacts on Electricity Demand Load and CO2 Emissions in Aceh Province to Achieve Net Zero Emission Target by 2060 - Hidayat, Taufik; Purwanto, Widodo Wahyu (Journal of Materials Exploration and Findings, 2026)
The electrification of the transport sector is a crucial pathway for achieving Indonesia’s Net Zero Emissions (NZE) target by 2060. This study assesses the potential impact of passenger electric vehicle (EV) penetration on electricity demand and CO2 emissions in Aceh Province through a scenario-based modelling approach. Two policy-aligned scenarios are assessed: a low-penetration (LP) scenario and a high-penetration (HP) scenario. Using the Gompertz model and the ASIF framework, total CO2 emissions were projected from 2020 to 2060. Results show that although higher EV penetration reduces direct emissions from internal combustion engine (ICE) vehicles, total CO2 emissions increase more significantly under LP scenario, reaching over 8.1 million tons by 2060, compared to 4.7 million tons in HP scenario. The increase in electricity demand resulting from EV adoption, if met by fossil-based power, can offset the environmental benefits. Thus, EV deployment must be aligned with power sector decarbonization through the adoption of renewable energy sources, grid upgrades, and clean charging infrastructure. Integrated transport-energy planning is vital to ensure that EVs support Indonesia’s NZE targets, particularly in regions like Aceh, which has untapped renewable potential.